KONTRIBUSI KELENTUKAN TOGOK DAN KESEIMBANGAN TERHADAP KETERAMPILAN HEADING BOLA - Saharullah Saharullah; Resky Pangestu; Andi Atssam Mappanyukki; Muhammadong Muhammadong (Perkumpulan Dosen Muda Bengkulu, 2023)
The results of the regression analysis of hit flexibility on heading skills in the U-16 Soccer School Students of Sheikh Yusuf, Gowa Regency, obtained a value of r = 0.137 (P = 0.000 α 0.05), then H0 was rejected and H1 was accepted, meaning that there was a significant contribution of hit flexibility to heading skills in the students of the U-16 Football School of Sheikh Yusuf, Gowa Regency. 6 (P = 0.000 α 0.05), then H0 is rejected and H1 is accepted, meaning that there is a balanced contribution to Heading Skills in the U-16 Syekh Yusuf Soccer School Students, Gowa Regency and if these two research variables are combined harmoniously, it means that it will have a positive influence on changes in the regression value of flexibility and balance on heading skills in the U-16 U-16 U-16 Sheikh Yusuf Football School Students in Gowa Regency with a regression R value of 0.156 (P = 0.000 α 0, 05).